Ignition System Practical Competency Improvement Through Problem-Based Learning Model Class XI Light Vehicle Engineering SMK Negeri 1 Palangka Raya - Yusep Yusep (LPPM Institut Studi Islam Sunan Doe, 2024)
This research is a Classroom Action Research, which aims to determine the increase in Competency Practices in the Ignition System Subject through a Problem-Based Learning Model for Class XI Light Vehicle Engineering students at SMK Negeri 1 Palangka Raya. The research subjects totaled 21 students. This research was conducted in 2 cycles, each 1 cycle was carried out in 4 meetings. The results of the research in cycle I and cycle II were (1) students who attended lessons on time increased by 7.13%, (2) students who answered questions increased by 1.98%, (3) students asking questions increased by 3.15 % (4) students collecting assignments on time increased by 5.95%, (5) carrying out other activities during the teaching and learning process such as fuss and messing around decreased by 25.39%, (6) taking notes on subject matter/ making resumes increased by 29.37%, (7) students who were late for lessons decreased by 8.06%. Prior to the application of the problem-based learning model the average pretest score was 56.90, but after the application of the problem-based learning model the average student score became 72.57 in cycle I and 79.00 in cycle II.